Characterization of Microstructure, Optical Properties, and Mechanical Behavior of a Temporary 3D Printing Resin: Impact of Post-Curing Time - Siqueira, Joyce Roma Correia dos Santos [UNESP]; Rodriguez, Rita Maria Morejon [UNESP]; Campos, Tiago Moreira Bastos; Ramos, Nathalia de Carvalho [UNESP]; Bottino, Marco Antonio [UNESP]; Tribst, João Paulo Mendes (MDPI, 2024)
The present study aimed to characterize the microstructure of a temporary 3D printing polymer-based composite material (Resilab Temp), evaluating its optical properties and mechanical behavior according to different post-curing times. For the analysis of the surface microstructure and establishment of the best printing pattern, samples in bar format following ISO 4049 (25 × 10 × 3 mm) were designed in CAD software (Rhinoceros 6.0), printed on a W3D printer (Wilcos), and light-cured in Anycubic Photon for different lengths of time (no post-curing, 16 min, 32 min, and 60 min). For the structural characterization, analyses were carried out using Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The mechanical behavior of this polymer-based composite material was determined based on flexural strength tests and Knoop microhardness. Color and translucency analysis were performed using a spectrophotometer (VITA Easy Shade Advanced 4.0), which was then evaluated in CIELab, using gray, black, and white backgrounds. All analyses were performed immediately after making the samples and repeated after thermal aging over two thousand cycles (5–55 °C). The results obtained were statistically analyzed with a significance level of 5%. FT-IR analysis showed about a 46% degree of conversion on the surface and 37% in the center of the resin sample. The flexural strength was higher for the groups polymerized for 32 min and 1 h, while the Knoop microhardness did not show a statistical difference between the groups. Color and translucency analysis also did not show statistical differences between groups. According to all of the analyses carried out in this study, for the evaluated material, a post-polymerization time of 1 h should be suggested to improve the mechanical performance of 3D-printed devices.
Keywords: 3D print; 3D printed resins; additive manufacturing; dental materials; monomers